DNA Base Complexes of Platinum and the Antitumor Action of cis-Pt(NH₃)₂Cl₂ - Sporanzini, Robert A. (My University, 1980)
A previously unknown mode of binding of platinum complexes to the DNA bases is described. The binding mode is characteristic of cis and not trans-Pt(NH₃)₂Cl₂ and is thought to be related to the ability of cis compounds to form hydroxobridged dimers. It is suggested that the differing anticancer activity of cis and trans-Pt(NH₃)₂Cl₂ may result from this difference in chemistry which is based on the differing stereochemical requirements of cis and trans isomers.
Keywords: Chemistry; Chemistry